ANALYSIS OF DRIBLING ABILITY TO PLAY SOCCER IN PLAYERS AGED 10-12 YEARS AT SSB BAJO - Subair, Eqwin; Kahar, Irsan; Ahmad; Nur, Suaib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a quantitative descriptive study that aims to determine the level of dribbling ability to play soccer at the age of 10-12 years at SSB Bajo. The variable in this study is a single variable, namely the level of dribbling ability to play soccer at the age of 10-12 years at SSB Bajo. The population in this study were all soccer players aged 10-12 years at SSB Bajo totaling 30 people, the sampling technique was purposive sampling, namely certain considerations by the researcher. The sample in this study was 20 people. The results showed that the level of dribbling ability to play soccer at the age of 10-12 years at SSB Bajo was in the